Doped Keggin Heteropolyacids as Catalyst in the Solvent-free, Multicomponent Synthesis of Substituted 3,4-dihydropyrimidin-2-(1H)-ones - D'alessandro, Oriana (2012)
We report the use of V, Bi and Bi-V Keggin structure where Mo is partially replaced by V, Bi, and Bi and V, respectively, in the solvent-free multicomponent synthesis of 3,4-dihydropyrimidin-2-(1H)-ones by the Biginelli method. The incorporation of V, Bi and Bi-V in the structure of PMo notably increases the catalytic activity. The following correlation between the yields of the 3,4- dihydropyrimidin-2-(1H)-ones and the number of acidic sites of the catalysts was observed: PMoBiV > PMoV > PMoBi > PMo. The reaction experiments were performed in the absence of solvent, at 80ºC (1 h). Under these conditions and using the most active catalyst (PMoBiV), twelve examples were obtained with very good yields (80-98%) and high selectivity. The catalyst was easily recycled and reused without appreciable loss of its catalytic activity. The synthetic method presented is a simple, clean and environmentally friendly alternative for the obtention of substituted 3,4-dihydropyrimidin-2-(1H)-ones.